Factors Inhibiting Lack of Interest in Reading among Middle School Students in Class VIII - Diana, Vina Aris; Markhamah, M (Universitas Muhammadiyah Surakarta, 2023)
The main question of this research is what is the reading interest of class VIII junior high school students and what factors influence the reading interest of class VIII junior high school students. The aim of this research is to explain the reading interest of class VIII junior high school students, the factors inhibiting class VIII junior high school students' interest in reading, and increase reading interest in class VIII junior high school students. This type of research is descriptive and qualitative. Data collection techniques were carried out through interviews and observation. Based on the research results, there are two factors that hinder students' interest in reading, namely internal factors such as the inability to read fluently, lack of motivation and reading habits, as well as lack of understanding of the content being read and external factors, an unsupportive school environment is one of the causal factors, Economics family, lack of equipment, and students' habit of playing with devices.